RACHEL WHITEREAD: QUESTIONS FOR ARCHITECTURE: QUESTIONAMENTOS PARA ARQUITETURA - Neiva, Simone (2022)
The article has as its object the dialogue between architecture and art in the work of British artist Rachel Whiteread. Its premise is the reordering of the traditional categories of art and the reconfiguration of the boundaries of sculpture towards a field shared between art, architecture (and landscape) proposed by Rosalind Krauss. The article proposes the questioning of fundamental prerogatives of architecture, such as: the relationship of space with the body; the habitability; the specificity of the place; the sense of permanence and functionality. At the end, we present as a contribution to the debate the idea of a possible self-reflection of architecture from Whiteread's sculpture.